Noble Metal Decoration and Presulfation on TiO2: Increased Photocatalytic Activity and Efficient Esterification of n-Butanol with Citric Acid. (2nd March 2016) - Niu, Yu; Huang, Pan; Li, Fuying; Yang, Kai; Yang, Jinbei; Wang, Renzhang; Lin, Cheng; Qiu, Ting
Abstract : TiO2 has been widely used as a key catalyst in photocatalytic reactions; it also shows good catalytic activity for esterification reactions. Different sulfated M-TiO2 nanoparticles (M = Ag, Au, Rh, and Pt) were prepared by photodeposition and ultrasonic methods. The results show that the noble metal nanoparticles, which were loaded onto a TiO2 surface, slightly affected the crystal phase and particle size of TiO2 . Among all the catalysts, S O 4 2 - /Au-TiO2 exhibited the best catalytic activity in the esterification reaction for the synthesis of citric acid n -butyl acetate and in the decomposition of methyl orange, as confirmed by a high conversion rate of up to 98.2% and 100% degradation rate, respectively. This can be attributed to an increase in the Lewis acidity of the catalyst and increased separation efficiency of electron-hole pairs. This superior catalyst has great potential applications in esterification reactions and wastewater treatments.